RESEARCH ON THE CRACKING MECHANISM OF THE MAIN GIRDER OF 350T CASTING CRANE - WANG XiaoXi; LUO HuiXin; DANG Zhang; XU WeiWen; ZHANG QinFen (Jixie qiangdu)
The problem of crack in the end of the crane girder is analyzed by using the 350 t casting crane in a steel plant.The finite element model is verified by the results of stress measurement. The finite element model is correct and the most dangerous condition of the main beam is analyzed. The results show that the maximum stress appears at the end of the main beam. According to the actual observation,the results of the finite element calculation,that the end of the main beam of the lower end of the curved plate,the end of the beam and the main beam end bending plate butt weld in the intersection,the stress concentration of the site,resulting in a crack in the main girder of crane. Finally,the reinforcement scheme is put forward,and the results show that the reinforcement effect is very significant.